Audit of antenatal care at a community health centre in Tshwane North subdistrict, Gauteng province - V. Horner; P.G.D. Rautenbach; T.J. Mashamba; N. Mbananga; S. Olorunju; T. Ramahlo; H. Kwinda (South African Family Practice, 2014)
Objective: Few studies document the level of compliance with antenatal care protocols in primary health care in South Africa. The aim of this study was to conduct an audit of antenatal care at a community health centre in Tshwane North subdistrict in order to measure the level of compliance of maternity staff with antenatal care protocols. This study was part of a larger study on a quality improvement initiative in primary health care.